How Four Health Plans Manage Biotech Drugs - CARLSON, BOB (BioCommunications LLC, 2004)
With the number of market-approved biotech drugs approved by the U.S. Food and Drug Administration expected to jump soon, health plans are scrambling to redesign benefit structures, manage utilization, and get a handle on the costs of these new therapies. Here’s how four health plans are addressing these issues.